Legal aspect of Islamic banking: a case study of Bahrain - Mohamed Nafees, Seeni Mohamed; Ahmad, Muhamad Hassan; Masum, Ahmad; Md. Dahlan, Nuarrual Hilal (Serials Publications (P) Ltd., 2018)
Kingdom of Bahrain is considered one of the leading countries in the Middle East where Islamic banking is growing enormously adopting various legal changes necessary to provide a level playing field to the Islamic banking industry. In order to pave the road to smooth running of the industry, innovative and legislative arrangements are introduced from time to time. Notably, the government of Bahrain strives to set it as an international hub for Islamic banking. As such, the Bahrain may be considered as an ideal model for countries which are involved in developing Islamic banking in their respective countries. Eventually, the study finds that Bahrain has introduced various legal changes as well as mandated the adherence to Shariah Standards of Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) for smooth running of Islamic banking industry which can be adoptable by other jurisdictions.